Quriosity Terhadap Kemampuan Literasi Sains Pada Ruang Lingkup Biologi UIN Syahada Padangsidimpuan - Hotmaidah Hasibuan (Institut Agama Islam Negeri, 2022)
Curiosity is necessary to live in today's world, so as not to be left behind by information that is developing very rapidly. Curiosity about literacy is a necessity for every human being who is human-centered and collaborates with technology. One of the important literacy in this era is scientific literacy. This study aims to describe comprehensively about curiosity towards scientific literacy. The research population was all students of the biology education study program in semesters 3 and 5 of FTIK UIN SYAHADA Padangsidimpuan, totaling 42 people. Sampling in this study was carried out by means of random sampling with a total sample of 20 people. This type of research is qualitative. The data collection technique was carried out by distributing questionnaires online using the Google form application Data analysis techniques using qualitative analysis. The results of data analysis show that overall student curiosity (curiosity) is classified as 'good', this is indicated by the number of students who choose 'always and often' for positive statements and those who choose 'rarely and never' for negative statements are less This study shows that there is good curiosity about scientific literacy in the material scope of biology